EFFECTIVENESS OF UP4 (Public Service Complaint Management Unit) IN PUBLIC SERVICE COMPLAINTS KENDAL DISTRICT - Alvissukri Anni ami; Hardi Warsono (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
UP4 (Public Service Complaint Management Unit) is a public service complaint management unit owned by the Kendal Regency government. The concept of good governance is present as one way out in solving problems from several demands in the community, and is expected to be able to to overcome any problems that arise in the process of public service. Through UP4 (Public Service Complaint Management Unit) complaints from various OPDs (Regional Apparatus Organizations) through various media channels that are integrated in stages, the implementation of autonomy can run properly and can be handled quickly, transparently, and accountably in accordance with the authority of each organizer. . The purpose of this study was to determine the effectiveness of UP4 (Public Service Complaint Management Unit) in public service complaints in Kendal Regency and to find out the factors constraining UP4 (Public Service Complaint Management Unit) in public service complaints in Kendal Regency. The research method is descriptive qualitative, with data analysis methods according to Miles and Huberman. The results showed that the UP4 (Public Service Complaint Management Unit) in Kendal Regency had not been running effectively, seen using indicators of input, process and output. The factor constraining UP4 is limited resources, which causes the community to not receive timely responses to complaints. Complaints based online, complaint reports should also be transparent through online media. The results of this study recommend forming a special team for the confirmation and data collection process, there is clear data transparency to the public regarding complaint data, there is a need for additional human resources to handle and manage complaints.